2014
DOI: 10.3892/or.2014.3591
|View full text |Cite|
|
Sign up to set email alerts
|

Synthetic miR-145 mimic inhibits multiple myeloma cell growth in vitro and in vivo

Abstract: Multiple myeloma (MM) is a disease with an adverse outcome and new therapeutic strategies are required to combat this disease. It is well known that tumor‑suppressor microRNA (miRNA) acts as a new potential anticancer agent. Accumulating evidence showed that microRNA-145 (miR-145) is a candidate tumor suppressor miRNA. However, whether miR-145 is involved in the development and progression of MM reamins to be determined. In the present study, we investigated the therapeutic potential of synthetic miR-145 again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…PI3K, a heterodimer, includes both catalytic subunit (p110) and regulatory subunit (p85) 32. The AKT/PI3K pathway is stated to be oncogenic, which influences cell proliferation and cell apoptosis in cancers, and has been found to be downregulated by overexpressed miR-145 to inhibit cell growth and promote cell apoptosis in tumor development 33. This study found that with increased miR-145 in IPA, there were decreased mRNA and protein expressions of PI3K and AKT3, where IPA cell proliferation, migration and invasion were inhibited while cell apoptosis was promoted.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K, a heterodimer, includes both catalytic subunit (p110) and regulatory subunit (p85) 32. The AKT/PI3K pathway is stated to be oncogenic, which influences cell proliferation and cell apoptosis in cancers, and has been found to be downregulated by overexpressed miR-145 to inhibit cell growth and promote cell apoptosis in tumor development 33. This study found that with increased miR-145 in IPA, there were decreased mRNA and protein expressions of PI3K and AKT3, where IPA cell proliferation, migration and invasion were inhibited while cell apoptosis was promoted.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study demonstrated that the EGFR inhibitor suppressed the EGFR/PI3K/AKT signaling pathway and increased the anticancer effects of miR-145 upregulation in A549 cells. Zhang et al (26) reported that synthetic miR-145 expression inhibits multiple myeloma cell growth through the PI3K/AKT signaling pathway. The present study only investigated the effect of the EGFR inhibitor on miR-145 upregulation in A549 cells, therefore future studies should also explore the effect of miR-145 inhibitors combined with EGFR inhibitors in A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that miR-145-5p can regulate apoptosis of osteosarcoma cells and play a therapeutic role, suggesting that miR-145 is a potential therapeutic target to interfere with the invasion, proliferation, apoptosis and other biological processes of the disease [9,10]. MiR-145-3p expression levels and the possibility of being a diagnosis and prognosis marker are not particularly clear in osteosarcoma [11]. The regulation of apoptosis and autophagy has yet to be defined.…”
Section: Introductionmentioning
confidence: 99%